2016
DOI: 10.1016/j.heliyon.2016.e00093
|View full text |Cite
|
Sign up to set email alerts
|

Influence of starter culture and a protease on the generation of ACE-inhibitory and antioxidant bioactive nitrogen compounds in Iberian dry-fermented sausage “salchichón”

Abstract: The effect of the addition of an autochthonous starter culture and the protease EPg222 on the generation of angiotensin-I–converting enzyme (ACE)-inhibitory and antioxidant compounds by the dry-fermented sausage “salchichón” was investigated. Sausages were prepared with purified EPg222 and Pediococcus acidilactici MS200 and Staphylococcus vitulus RS34 as the starter culture (P200S34), separately and together, ripened for 90 days, and compared to a control batch. Among the ripening time points (20, 35, 65, 90 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 60 publications
1
12
0
2
Order By: Relevance
“…Flores and Toldra (2011) reported that the microorganisms, including LAB, generate oligopeptides and free amino acids that inhibit ACE. Fernández et al (2016) also found that ACEinhibitory activity in dry fermented sausages "salchichón" is influenced by the starter culture strain. Mejri et al (2017a) have reported high ACE-inhibitory activity of small peptides of <3 kDa molecular weight released during camel sausage fermentation.…”
Section: α-Amylase and α-Glucosidase Inhibitory Activitiesmentioning
confidence: 89%
“…Flores and Toldra (2011) reported that the microorganisms, including LAB, generate oligopeptides and free amino acids that inhibit ACE. Fernández et al (2016) also found that ACEinhibitory activity in dry fermented sausages "salchichón" is influenced by the starter culture strain. Mejri et al (2017a) have reported high ACE-inhibitory activity of small peptides of <3 kDa molecular weight released during camel sausage fermentation.…”
Section: α-Amylase and α-Glucosidase Inhibitory Activitiesmentioning
confidence: 89%
“…Peptides that act as antihypertensives are thought to be competitive substrates for the inhibition of angiotensin I-converting enzyme, which plays a key role in the regulation of blood pressure. Hydrophobic amino acid residues such as arginine, lysine, or proline in the C-terminal position of the peptide (Vermeirssen, Van Camp, & Verstraete, 2004;Meisel, 2005;Fernández et al, 2016) are helpful in the ACE-inhibiting activity.…”
Section: Bioactive Peptides: Technological Applicationmentioning
confidence: 99%
“…However, studies show that microorganisms other than LAB such as Bacillus spp. [ 22 , 34 ] Staphylococcus vitulus [ 80 ], Saccharomyces cerevisiae [ 5 , 21 , 81 ], Debaryomyces hansenii [ 82 ], Mucor spp. [ 83 ], and Aspergillus spp.…”
Section: Production Of Ace-inhibitory Peptides From Plantsmentioning
confidence: 99%
“…Starter cultures, fermentation conditions and inoculum levels play important roles in ACE-inhibitory peptide production [ 21 , 79 , 80 ]. Shu et al [ 79 ] reported that ACE-inhibitory activity increased with fermentation time in milk fermented by Lactobacillus plantarum , as reported in mao–tofu fermented by Mucor spp.…”
Section: Production Of Ace-inhibitory Peptides From Plantsmentioning
confidence: 99%